The use of modern technologies by foreign language teachers: developing digital skills - Biletska, Iryna O.; Paladieva, Alla F.; Avchinnikova, Halyna D.; Kazak, Yuliia Yu. (Linguistics and Culture Review, 2021)
In recent years, the question of using new information technologies in the education system has been increasingly raised. These are not only new technical means but also new forms and methods of teaching, a new approach to the learning process. The purpose of this study consisted in developing a program for teaching future foreign language teachers using digital technologies. In this study, a descriptive and analytical methods were used. Analysis of specialised literature on research topics as well as of training programs for future teachers of a foreign language was conducted. A system of classes for future teachers of a foreign language for a semester in the subject “English” and a number of recommendations for creating a course and conducting classes using digital technologies has been developed. A pilot study that showed the effectiveness of these techniques was conducted. It was found that thanks to the authors’ approach the students can complete the tasks assigned to them more quickly and learn how to correctly apply new tools in their work.